2019
DOI: 10.1080/10253866.2018.1562701
|View full text |Cite
|
Sign up to set email alerts
|

“Superdisabilities” vs “disabilities”? Theorizing the role of ableism in (mis)representational mythology of disability in the marketplace

Abstract: Acknowledgement: The authors wish to express their thanks and appreciation to the Special Issue editors and the three anonymous reviewers for their insightful comments on the earlier versions of this manuscript. 2 'Super disabilities' vs 'Disabilities'? Theorizing the role of ableism in (mis)representational mythology of disability in the marketplace Abstract People with disabilities (PWD) constitute one of the largest minority groups with one in five people worldwide having a disability. While recognition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 66 publications
0
60
0
7
Order By: Relevance
“…Ou seja, promove a valorização dos sujeitos a partir de determinadas capacidades, que nem sempre são possíveis e/ou desejáveis para todos. Isto, por consequência, pode levar à desvalorização daqueles que não atingem os mesmos tipos e/ou níveis de capacidades (Kearney, Brittain, & Kipnis, 2019). Apesar destas críticas, escolhemos estes materiais porque eles contrastam com o imaginário de que as PCD são frágeis, doentes, dependentes e incapazes (Marques, 2016;Oliveira, Poffo, & Souza, 2018;Poffo et al, 2017).…”
Section: Métodosunclassified
“…Ou seja, promove a valorização dos sujeitos a partir de determinadas capacidades, que nem sempre são possíveis e/ou desejáveis para todos. Isto, por consequência, pode levar à desvalorização daqueles que não atingem os mesmos tipos e/ou níveis de capacidades (Kearney, Brittain, & Kipnis, 2019). Apesar destas críticas, escolhemos estes materiais porque eles contrastam com o imaginário de que as PCD são frágeis, doentes, dependentes e incapazes (Marques, 2016;Oliveira, Poffo, & Souza, 2018;Poffo et al, 2017).…”
Section: Métodosunclassified
“…On the other hand, it emphasises the potential to conquer disability through sheer hard work and effort, thereby underestimating the structural and attitudinal barriers that most people with an impairment face. Critics of the supercrip narrative argue that it diverts attention away from the real and material barriers facing people with a disability, offering audiences comfort that “super” para-athletes (superhumans) can carve out wonderful careers and overcome their disability (Ellis & Goggins, 2015; Grue, 2015; Kearney et al, 2019). As Silva and Howe (2012, p. 188) suggest, “By conveying the idea that all the dreams are possible depending on an individual’s effort and merit, the social injustice of unequal opportunities for ‘able’ and ‘disabled’ people is ignored.”…”
Section: From “Invisible” To “Incredible”: Paralympic Games and Media Framing Of Disabilitymentioning
confidence: 99%
“…Television coverage of the London 2012 Paralympic Games on the UK’s Channel 4 (hereafter C4) has been shown to have had a positive impact on how disability was covered in the media, especially in communicating the social agenda message around influencing attitudes; creating a thrilling elite live sport event experience; and in enabling familiarity and neutralisation of difference in coverage (Hodges et al, 2014). However, previous research also suggested that there remained an overreliance on the narrative of “triumph over adversity” in television coverage and in how audiences responded to the Paralympic Games in 2012 (Ellis & Goggins, 2015; Grue, 2015; Kearney, Brittain, & Kipnis, 2019; Pullen, Jackson, Silk, & Scullion, 2019; Smith, Zhou, & Green, 2017).…”
mentioning
confidence: 99%
“…Importantly, in the context of institutionalizing complex and multi-faceted social meanings such as cultural diversity, consumers increasingly demand ongoing effort by brands and organizations to maintain cultural-cognitive legitimacy. In particular, consumers’ expectations of brands’ engagement with cultural diversity are evolving beyond a call for recognition and representation (for instance, Hispanic consumer groups - Peñaloza 1994), to influencing representations’ meanings for greater accuracy (for instance, backlashes against stereotyped representations of ethnic minorities – Mahtani 2001, people with disabilities – Kearney, Brittain, and Kipnis 2019, gay people – Tsai 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%